Atrial natriuretic peptide levels in the sleep apnoea/hypopnoea syndrome. Issue 9 (September 1994) - Mackay, T W; Fitzpatrick, M F; Freestone, S; Lee, M R; Douglas, N J
Abstract : BACKGROUND--Patients with the sleep apnoea/hypopnoea syndrome have increased salt and water excretion at night which has been reported to be associated with an increase in plasma levels of atrial natriuretic peptide (ANP). A study was performed to determine whether any rise in plasma ANP levels was related to nocturnal hypoxaemia. METHODS--Nine patients with sleep apnoea/hypopnoea syndrome were studied on two nights, one breathing air and the other 28% oxygen, the order being randomised. Venous levels of ANP, aldosterone, and renin activity were measured. RESULTS--No decrease in plasma ANP levels on oxygen was seen, and, indeed, there was no evidence of an overnight increase in ANP levels. CONCLUSION--Oxygen therapy does not diminish nocturnal plasma ANP levels in patients with sleep apnoea/hypopnoea syndrome.